Knowledge and outcome measure of HbA1c testing in Asian Indian patients with type 2 diabetes from a tertiary care center - Manoharan Deepa; Viswanathan Vijay; Kumpatla Satyavani; Medempudi Srikanth (Wolters Kluwer Medknow Publications, 2010)
Aim: HbA1c test is considered to be the reliable measure for evaluating long-term glycemic control in type 2 diabetes. The purpose of this study was to evaluate whether knowledge about HbA1c test is associated with a better glycemic control. Materials and Methods: We conducted a cross-sectional survey of 480 (M:F; 287:193) adults with type 2 diabetes attending a tertiary care center during a period of four months. Baseline demographic and clinical data of all the subjects was obtained. Subject′s knowledge about HbA1c test and their target goal was assessed using a questionnaire. Recent HbA1c results were obtained from medical records. Results: Seventy four per cent of the subjects had awareness about HbA1c test and about 43% of those who knew HbA1c test also knew their target goal. 33% remember their last HbA1c result. The mean A1C of Group A was significantly lower when compared with Group B (8.1 ± 1.7 vs 9.2 ± 1.9, P<0.0001). Group C had lower A1C levels compared to Group D (7.7 ± 1.4 vs 8.5 ± 1.9, p<0.0001). Patients who kept their HbA1c less than 7% were significantly higher in Group C than in Group D. (37.8 vs 12.7%, p<0.00001). Subjects had good glycemic control with increasing levels of awareness about HbA1c. Conclusion: Majority of the diabetic patients who attended the tertiary care center for diabetes care knew HbA1c test and half of them were aware about their target goal. Awareness about HbA1c had a positive impact on maintenance of better glycemic control.